2015
DOI: 10.4049/jimmunol.1500961
|View full text |Cite
|
Sign up to set email alerts
|

FLI1 Levels Impact CXCR3 Expression and Renal Infiltration of T Cells and Renal Glycosphingolipid Metabolism in the MRL/lpr Lupus Mouse Strain

Abstract: The ETS factor FLI1 is a key modulator of lupus disease expression. Over-expressing FLI1 in healthy mice, results in the development of an autoimmune kidney disease similar to that observed in lupus. Lowering the global levels of FLI1 in two lupus strains (Fli1+/−) significantly improved kidney disease and prolonged survival. T cells from MRL/lpr Fli1+/− lupus mice have reduced activation and IL-4 production, Neuraminidase1 (Neu1) expression, and the levels of the glycosphingolipid (GSL) lactosylceramide (LacC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…GSLs are enriched in the kidney and GSL metabolism is altered in several kidney diseases, including lupus nephritis [6,7,10,13]. GSL metabolism also was shown to be altered in T cells from patients with lupus [28][29][30][31] and in lupus mice [24,32]. Specifically, we demonstrated that in lupus mice, LacCers, GlcCers, and NEU activity levels were increased in the kidney of mice with worse proteinuria [13,14] and decreased in T cells of lupus mice with improved disease [24].…”
Section: Discussionmentioning
confidence: 63%
“…GSLs are enriched in the kidney and GSL metabolism is altered in several kidney diseases, including lupus nephritis [6,7,10,13]. GSL metabolism also was shown to be altered in T cells from patients with lupus [28][29][30][31] and in lupus mice [24,32]. Specifically, we demonstrated that in lupus mice, LacCers, GlcCers, and NEU activity levels were increased in the kidney of mice with worse proteinuria [13,14] and decreased in T cells of lupus mice with improved disease [24].…”
Section: Discussionmentioning
confidence: 63%
“…Findings in earlier reports indicated that expression of chemokines was relatively lower in MRL/lpr Fli-1 +/− mice [14]; this may result in an overall diminished degree of T cell chemotaxis and recruitment to the kidney. In fact, Sundararaj et al reported that FLi-1 impacts MRL/lpr lupus nephritis through direct regulation of chemokine (C-X-C) motif receptor 3 (CXCR3) to reduce T cell activation, migration, and downregulation of CXCR3 ligands, Cxcl9 and Cxcl10 in the kidney [29]. CXCR3 plays an important role in mouse and human lupus, by regulating infiltration of Th1 and Th17 cells into the kidney [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…have displayed that an array of factors involved in glycerophospholipid metabolism, arachidonic acid metabolism and tryptophan metabolism pathways were activated during human hepatitis C virus infection and arachidonic acid metabolism was also an up-regulated marker of neuro-inflammation in HIV-1 transgenic rats [ 41 , 42 ]. Moreover, glycosphingolipid biosynthesis played an important role in nephritis development and CD1d-mediated lipid antigen presentation [ 43 , 44 ]. Glutamine is used in the tricarboxylic acid cycle and human cytomegalovirus infection could activate the mechanisms that switch the anaplerotic substrate from glucose to glutamine to meet the biosynthetic and energetic needs of the viral infection [ 45 ].…”
Section: Discussionmentioning
confidence: 99%